Islamic Religious Education in the Era of Disruption: Equipping Students with 21st Century Skills through the Project Learning - Siti Khumairotul Lutfiyah; Balqisa Ratu Nata; Hanun Asrohah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2025)
The era of disruption presents both challenges and opportunities for education, including Islamic Religious Education (PAI), which must be able to equip students with 21st century skills. This study aims to explore the application of project-based learning (PjBL) in developing these skills, especially on the theme of sharia buying and selling. The method used is qualitative through literature study by analyzing literature related to PjBL and PAI teaching in the digital era. The results showed that PjBL, through the learning by absorption and learning by reflection approaches, was able to develop these skills, especially on the theme of sharia buying and selling, was able to improve students' understanding of the concept of sharia buying and selling while honing skills such as critical thinking, creativity, communication, and collaboration. In implementation, students are actively involved in projects that integrate Islamic values with real-world challenges, such as simulations of Islamic values with real-life challenges, such as a sharia market simulation or an educational video. The conclusion of this study is that PjBL is not only not only relevant to improve the quality of PAI learning but also effective in shaping students' adaptive and innovative characters. Thus, PjBL makes a significant contribution in preparing a generation that is capable of face the challenges of the disruption era and still adhere to religious values.